2020
DOI: 10.1007/s11764-020-00963-y
|View full text |Cite
|
Sign up to set email alerts
|

Social support and physical activity for cancer survivors: a qualitative review and meta-study

Abstract: Physical activity (PA) is important for well-being and coping among cancer survivors. Social support (SS) encourages adoption and maintenance of PA behaviour, and PA contexts can provide opportunities for obtaining support for coping with cancer. The qualitative literature examining cancer survivors' experience with SS in and for PA could inform understanding of behaviors experienced as supportive. The purpose of this meta-study was to synthesize the research on adult cancer survivors' experiences with SS rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 65 publications
5
41
1
Order By: Relevance
“…Patients with advanced cancer who have engaged in professionally supervised, structured exercise interventions with other people with cancer often report positive experiences [ 58 62 ]. Indeed, prior research suggests physical activity or exercise interventions among people with cancer can provide opportunities to build relationships and provides a shared experience that is positive [ 63 ]. Our findings support that exercise interventions specifically for people with cancer may offer social benefits, as participants discussed their potential to foster social connectedness and create a sense of normalcy.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with advanced cancer who have engaged in professionally supervised, structured exercise interventions with other people with cancer often report positive experiences [ 58 62 ]. Indeed, prior research suggests physical activity or exercise interventions among people with cancer can provide opportunities to build relationships and provides a shared experience that is positive [ 63 ]. Our findings support that exercise interventions specifically for people with cancer may offer social benefits, as participants discussed their potential to foster social connectedness and create a sense of normalcy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-study revealed social support can facilitate PA motivation in cancer patients [ 15 ], and diverse studies provided evidence of the positive associations between social support and PA [ 16 ]. Social support is complex and multi-facet [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…They focused on opportunities and not limitations. In relation with a meta-study, which recognized the importance of replacing disease-focused follow-up care with wellness-focused survivorship care (13). The sense of fellowship and understanding by peers, the participants experienced the peer support during training sessions as encouraging and motivated them to achieve a higher intensity and maximized their bene t.They also helped regulate each other's intensity, when their exercise partner had a bad day and/or lack of energy.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of support, information and recommendations from health care professionals, treatment side effect, lack of time and motivation, feeling uncomfortable in a tness center due to changed appearance and physical level after treatment are common barriers due to reduced PE levels post treatment (11,12). However, cancer survivors show a high level of interest in participating in health promoting exercise programs and exercise interventions (6,13,14), but adherence to exercise program and maintenance after interventions seems to be challenging (15,16). Exercise adherence and maintenance is affected by multiple factors including sociodemographic, physical and medical variables (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation